La educación en la Odontología. Fundamentaciones inherentes del multimedio educativo para uso en el proceso enseñanza aprendizaje en las escuelas dentales. - Maroto M., Orlando; Chan Rodríguez, José (Odovtos - International Journal of Dental Sciences, 2011)
This article deals with the fundamental characteristics required for the educational mul-timedia in order to use put in the learning process in dental schools. These require more than a theoretical content, and images and audio resources are needed in order to obtain a pedagogical product with a structu-red form for the specific user. Some software makes it easy to develop multime-dia. However without adequate fundamental development the result will be a irrelevant to the intended purpose.